A role for putamen in phonological processing in children*. Issue 2 (24th June 2016) - CHERODATH, SARIKA; RAO, CHAITRA; MIDHA, RASHI; T A, SUMATHI; SINGH, NANDINI C
Abstract : Bilingual children are required to successfully develop phonological skills in two languages, yet little is known about the neural correlates associated with them. We obtained structural imaging data from 30 Hindi–English children aged between 8 and 10 years and used voxel based morphometry to explore neuroanatomical correlates of behavioural measures of phonological awareness. Our results showed that phonological skills in English are predicted by grey matter volume of bilateral putamen, but solely by right putamen in Hindi. Post-hoc analysis revealed that English nonword reading correlates with grey matter volume in bilateral putamen while in Hindi nonword reading it correlates only with right putamen. These differences in putamen-based mechanisms indicate that syllable level awareness sufficiently supports early literacy in the transparent, alphasyllabic Hindi orthography whereas that in English requires both phonemic and syllabic level awareness. Our findings point towards a key role for putamen in mediating phonological and reading skills in children.